Suggested alternatives for funding higher education in Saudi Arabia in light of the experiences of some developed countries - Al Shanifi, Ali bin Abdullah (Journal of Educational and Psychological Sciences, 2018)
This study aimed to provide proposed alternatives to finance higher education in Saudi Arabia in the light of the experiences of some developed countries (USA, Germany, Japan) to make use of them as much as possible in finding resources to finance higher education in Saudi Arabia; Higher education institutions in the Kingdom of Saudi Arabia, and keeping abreast of recent developments, by taking advantage of the experiences of some developed countries to improve the financing of higher education in the Kingdom of Saudi Arabia, which has high rates of expenditure on higher education continuously, The study included descriptive analytical method.The study found that the most important sources of funding for higher education in Saudi Arabia are the government, followed by other sources of funding such as individuals and loans, private and local sources, and external sources. The study also found alternatives to funding higher education, taking into account social, In light of the experiences of developed countries. The most important of these alternatives are the development of human resources, financial resources and educational resources, interest in technological incubators, increasing research chairs, the trend towards privatizing higher education, Ml.The most important recommendations of the study were to emphasize the importance of sound and comprehensive planning for the development needs of the labor force of graduates, linking them to the labor market, granting the universities sufficient financial and administrative powers to invest their resources, reducing the financial burden of the state budget from supporting higher education, The supervision and control of the government, the rationalization of the tunnels on higher education institutions, the reduction of cost, and finally the conversion of universities to production, investment and development centers.
Keywords: suggested alternatives; financing; higher education; experiences of some developed countries